O ensino da prosódia gráfica para surdos no nível fundamental - BARROS, Débora da Silva (2021)
With the objective of contributing for the progress of the studies about the bilingual education for deaf, it is investigated in this work how it happens the process of teaching-learning of the graphic prosody for deaf students in the level fundamental slant of analysis of contents of Portuguese language suggested for the 6th year of the fundamental teaching, 1 (one) plan of course of Portuguese language and an individual daily plan of the Specialized Education Service supplied by 2 (two) public schools of the municipal district of Tomé-Açu that assist students listener and deaf enrolled in the 6th year of the fundamental teaching. and interviews accomplished with 4 (four) teachers that assist deaf students in the regular teaching and in the specialized education service. The methodology used for research if it based on the document analysis and in interviews, and through the collected data, we lifted discussion showing that the teaching of the punctuation marks for deaf students needs to be accomplished with the use of visual resources and what is necessary the teacher to know the Language of Signs to promote interaction in classroom.